Habit and Affect: Revitalizing a Forgotten History. (June 2013) - Blackman, Lisa
Habit is an integral concept for body studies, a hybrid concept and one that has provided the bedrock across the humanities for considering the interrelationships between movement and stasis, being and becoming, and process and fixity. Habits are seen to provide relay points between what is taken to be inside and outside, disrupting any clear and distinct boundary between nature and culture, self and other, the psychological and social, and even mind and matter. Habit thus discloses a paradox. It takes up a unique position in affect modulation, which encompasses both regulation (in the form of discipline) and also extends the body's potential for engaging the new, change and creativity. In order to understand the basis of the ambivalent duality governing understandings of habit it is argued that a genealogical approach to this question is necessary. This will be located within the recent 'turn to affect' and histories of conation within the psychological sciences, particularly taking the writings of William McDougall as a focus.